Formação de professores: letramentos literário e digital em aulas de língua portuguesa - Carvalho, Lyedja Symea Ferreira Barros (Universidade do Vale do Rio dos Sinos, 2025)
This thesis examines how the integration of literary literacy, digital literacy, and teacher education can enhance the development of literary readers in the final years of Elementary School. Conducted in partnership with public school teachers, the study involved formative workshops based on the Reading in Digital Environments Didactic Framework (LIDDA) and the creation of a learning community. The research followed the principles of action research, emphasizing listening, collaboration, and the transformation of teaching practices.Findings indicate that while teachers demonstrated fluency in the personal use of digital technologies, they faced challenges in applying these tools pedagogically. The workshops enabled the design of original lesson plans that combined literary reading with pedagogical mediation and the intentional use of digital resources. The establishment of a collaborative Padlet and a WhatsApp community fostered experience sharing, the consolidation of formative bonds, and the strengthening of teacher authorship. A collaborative e-book emerged as a concrete outcome, compiling innovative practices that integrate literature and technology.Grounded in solid theoretical frameworks — including Cosson (2006), Freire (1996), Kersch (2020, 2024), Azevedo; Kersch (2024), Nóvoa (2023), and the Brazilian National Common Core Curriculum (BNCC, 2018) — and informed by the DigCompEdu (Lucas; Moreira, 2018) and SAMR (Puentedura, 2006) models, the study demonstrates that critically mediated digital technologies can promote meaningful pedagogical transformations. Moreover, it broadens students’ engagement, fostering active participation in reading, aesthetic appreciation, and meaning-making.
Keywords: Letramento literário; Letramento digital; Formação docente; Comunidade de aprendizagem; Literary literacy; Digital literacy; Teacher training; Learning community; ACCNPQ::Lingüística, Letras e Artes::Lingüística